Search and Comparison of Isim Ma'rifat with Remove Diacritic in the Qur'an and Hadith of Abu Daud - Teuku Muhammad Ikhsan; Eko Darwiyanto; Moch Arif Bijaksana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This research aims to address the issues of searching for and comparing Isim Ma'rifat (definite nouns) with the prefix